2014
DOI: 10.1158/1535-7163.mct-14-0074
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Silencing of KRAS Using Systemically Delivered siRNAs

Abstract: Despite being amongst the most common oncogenes in human cancer, to date there are no effective clinical options for inhibiting KRAS activity. We investigated whether systemically delivered KRAS siRNAs have therapeutic potential in KRAS mutated cancer models. We identified KRAS siRNA sequences with notable potency in knocking-down KRAS expression. Using lung and colon adenocarcinoma cell lines, we assessed anti-proliferative effects of KRAS silencing in vitro. For in vivo experiments, we used a nano-liposomal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 25 publications
1
64
0
Order By: Relevance
“…As in previous reports, which showed that knockdown of KRAS RNA expression with siRNA against the target RNA impeded the growth of human tumor cells harboring the mutant KRAS gene in vivo, 43 reduction of the KRAS G12V RNA expression by the specific ribozymes alone retarded the growth of tumors harboring the mutant KRAS gene in cell cultures as well as in vivo. A slight reduction in the level of wild-type KRAS transcripts (33%-39%) by the ribozyme-encoding adenoviruses was observed in cells harboring wild-type gene, probably due to antisense effects induced by the ribozyme, but it did not affect the growth of cells.…”
Section: Wwwmoleculartherapyorgsupporting
confidence: 72%
“…As in previous reports, which showed that knockdown of KRAS RNA expression with siRNA against the target RNA impeded the growth of human tumor cells harboring the mutant KRAS gene in vivo, 43 reduction of the KRAS G12V RNA expression by the specific ribozymes alone retarded the growth of tumors harboring the mutant KRAS gene in cell cultures as well as in vivo. A slight reduction in the level of wild-type KRAS transcripts (33%-39%) by the ribozyme-encoding adenoviruses was observed in cells harboring wild-type gene, probably due to antisense effects induced by the ribozyme, but it did not affect the growth of cells.…”
Section: Wwwmoleculartherapyorgsupporting
confidence: 72%
“…RAF or PI3K effectors) (Fruman and Rommel, 2014;Samatar and Poulikakos, 2014), (iv) inhibitors of processes that support the increased metabolic needs of cancer cells (e.g. macropinocytosis, autophagy, glucose and glutamine metabolism), (v) unbiased genetic or chemical screens for synthetic lethal interactors Kumar et al, 2012;Luo et al, 2009;Sarthy et al, 2007;Scholl et al, 2009) and (vi) RNA interference (RNAi) of KRAS expression (Pecot et al, 2014;Xue et al, 2014;Yuan et al, 2014).…”
Section: Box 2 Approaches For Targeting Rasmentioning
confidence: 99%
“…Other promising approaches are currently being explored, such as RAS-mediated changes in cell metabolism and RAS gene silencing2 by the application of miRNAs or siRNA7. We have previously demonstrated that miR-143 reduces KRAS expression, chemo-sensitizes colon cancer cells to 5-fluorouracil8 and reduces tumour growth in vivo with increased apoptosis and reduced proliferation9.…”
mentioning
confidence: 99%